(untitled) (Portuguese Journal of Family Medicine and General Practice, 2022)
Introduction: Respiratory diseases are a major cause of morbidity in the pediatric population. Nebulizers, for years the most suitable devices for administering aerosol therapy in children, have been superseded by simple inhalation devices. Current clinical guidelines restrict the prescription and use of nebulizers. The study aims to investigate the reality of domiciliary use of nebulizing systems in the pediatric age in the São Miguel Island Health Unit. Methods: Observational, analytical, and cross-sectional study. Inclusion criteria: children from zero to seven years and 365 days of age. A face-to-face survey was performed on caregivers of the target population to assess the context of the acquisition, use, and maintenance of nebulizers. A significant sample of 380 users was calculated (95% confidence interval). Results: Participation of 387 caregivers. The average age of children included 2.5 years. 45,7% of participants had a nebulizer and 18,9% reported having a simple inhaler device. The rate of acquisition and use of nebulizers without medical prescription was 67.8% and 79.7%, respectively. The cost of acquiring the nebulization system was between 80 and 150 euros for 38.4% of the participants. Most of the unsupervised use occurred with saline and in the context of nasal obstruction (41.1%) and cough (24.9%). Discussion: The present study reveals an excessive, unsupervised and inappropriate use of nebulizers in pediatric age. The present investigation should encourage the promotion of the use of simple inhaler devices, by educating users, caregivers, and health professionals, aiming to improve local health practice.